ELECTRONEGATIVE ELECTRORETINOGRAM IN ACHROMATOPSIA. Issue Volume 12:Issues 2(2018) (2018) - Schallhorn, Craig S.; Granet, David B.; Ferreyra, Henry A.
Abstract : Purpose: To report novel electroretinographic findings in a genetically confirmed case of achromatopsia. Methods: A patient with a history of childhood nystagmus, photoaversion, and absent color vision was examined. Electroretinography and fundus examination were performed under anesthesia at the time of corrective surgery for nystagmus. Genomic DNA isolated from peripheral blood was directly sequenced for variations in the CNGA3 and CNGB3 genes. Results: Ophthalmoscopic examination revealed no distinct abnormalities. Electroretinography obtained under anesthesia at age three years revealed absent photopic responses. The dark-adapted combined responses had reduced b-wave amplitudes resulting in an electronegative configuration. Genetic testing revealed two heterozygous sequence variations present in the coding sequence of the CNGA3 gene (Arg223Trp and Pro372Ser), which have been previously described in the setting of achromatopsia. Sequencing of the patient's parents confirmed that these two variations lie on separate alleles. Conclusion: Novel electroretinography findings in a patient with genetically confirmed achromatopsia are reported. The electronegative configuration in this clinical setting is of unclear etiology; however, it may suggest some component of inner retinal dysfunction. Abstract : A patient with genetically confirmed achromatopsia is presented with novel electroretinographic findings in an electronegative configuration.